A 32-year trend analysis of lower respiratory infections in children under 5: insights from the global burden of disease study 2021 - Wang, Yan; Han, Ruiyang; Ding, Xiao; Chen, Junli; Feng, Wenjia; Wang, Chunping; Gao, Runguo; Ma, Anning (Frontiers in Public Health, 2025)
ObjectivesLower respiratory infections are the most significant health threat to children under 5 years old, leading to the highest disease burden across all age groups. This study aims to provide an up-to-date assessment of the global burden of lower respiratory infections in children under 5 years of age.MethodsThis study utilizes data and methodologies from the Global Burden of Disease Study 2021 to analyze changes in the burden of lower respiratory infections from 1990 to 2021, focusing on incidence, mortality, and disability-adjusted life years. A jointpoint model is employed to calculate trends and the average annual percentage change in the disease burden among children under 5 years old over the period 1990–2021. Additionally, frontier analysis is used to visually depict the potential for burden reduction in each country or region based on their level of development.ResultsIn 2021, the global burden of lower respiratory infections in children under 5 years old included 37,828,159 incidence cases, 501,909.50 deaths, and 44,779,174.70 disability-adjusted life years. From 1990 to 2021, the global burden of LRIs in this age group showed a marked decline. Incidence, mortality, and disability-adjusted life years decreased by 54.02, 37.57, and 39.49%, respectively. The average annual percent change for age-standardized incidence rate, age-standardized mortality rate, and age-standardized disability-adjusted life years rate were −3.35, −4.53%, and −4.52%, respectively. The disease burden was notably higher in children under 1 year old compared to those aged 2–4 years and the overall under-5 age group, with significant gender differences observed. Additionally, there was a strong negative correlation between the burden of lower respiratory infections in children under 5 and the socio-demographic index. Frontier analysis indicated that countries or regions with higher socio-demographic index values showed greater potential for reducing the burden.ConclusionThe global burden of lower respiratory infections in children under 5 years old has declined significantly from 1990 to 2021. However, given the substantial disease burden, particularly in low-SDI countries, it is crucial to address risk factors and implement more effective interventions to further reduce the impact of lower respiratory infections on this vulnerable population.